The quality of parental participation and student achievement in Peruvian government schools - Balarin, M; Cueto, S (2007)
The paper presents and discusses the findings of a study on families’ and teachers’ understanding of parental involvement in children’s schooling in public primary schools in Peru. The study was undertaken against a background of encouragement of parental participation in education as a means to democratise and improve the quality of educational services. In Peru, as elsewhere, parental involvement in schooling is increasingly seen as contributing to learning and achievement. A sample of 16 children in four departments of Peru was interviewed, together with their teachers and parents. Researchers found parents have limited knowledge about how learning takes place in schools and how they can support their children. Hardly any schools have strategies to guide parental involvement in schooling. Understanding of learning is especially inadequate among poorer and less-educated families. The authors draw the attention of policy-makers to the need to develop better strategies to shape and promote parental involvement in ways that might help enhance children’s learning and achievement.